Alternative livelihood for bidi workers: a study based on primary research on home-based bidi rollers of Solapur city of Maharashtra - Supase, Ashish S.; Oswal, Kunal; Mukherjee, Kanchan; Singh, Ajita; Chaturvedi, Pankaj (International Journal Of Community Medicine And Public Health, 2020)
Background: Solapur city situated in the district of Solapur, is home to the largest number of bidi workers of Maharashtra. Women and children engaged in bidi rolling face abuse, financial domination and a varied range of occupational health concerns. The bidi workers thus emphasize the need for an alternative livelihood strategy. The research-based on the review of existing programs, policies, best practices and successful models (locally and globally) for developing an alternative livelihood, understand the magnitude of work satisfaction among bidi workers and their perspective on alternative livelihoods. Methods: Descriptive and cross-sectional study design was adopted to conduct the study using a semi-structured interview schedule using a mixed-method approach. Data collection was done with the help of in-depth interviews with the workers, members of workers’ association, individuals and other key informants. Content analysis, triangulation method and Microsoft Excel were used for the statistical analysis. Results: The preliminary finding of the research indicates that bidi workers have the willingness to change their profession but they can only be accomplished if the right opportunities are provided. If there is a provision of training, 90% of the respondents are interested in making the shift to an alternative livelihood. Conclusions: In this context, it is anticipated that the recommendation towards developing alternative livelihood option other than bidi rolling will help tackle the deplorable condition of the workers.